2021
DOI: 10.1186/s12935-020-01695-w
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0061395 accelerates hepatocellular carcinoma progression via regulation of the miR-877-5p/PIK3R3 axis

Abstract: Background Circular RNA hsa_circ_0061395 (circ_0061395) has been reported to accelerate the advancement of hepatocellular carcinoma (HCC). However, the regulatory mechanism by which circ_0061395 modulates the progression of HCC is unclear. Methods The morphology and size of exosomes were analyzed by transmission electron microscope (TEM) and nanoparticle-tracking analysis (NTA). Protein levels were detected by western blotting. Expression levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…It is found that miR-877-5p inhibits the cell proliferation, migration and invasion of hepatoma [40] and suppresses the cell growth of gastric carcinoma [39]. Also, more researches demonstrate that various long non-coding RNAs or circular RNAs facilitate the tumorgenesis of different carcinomas by decreasing the level of miR-877-5p [66][67][68][69][70], further verifying the suppressive effect of miR-877-5p in cancer development. In accordance with previous researches, the results of our experiments showed that TQ significantly upregulated the miR-877-5p expression level, and the inhibitor of miR-877-5p markedly upregulated the mRNA levels of CD274 (PD-L1), suggesting that CD274 mRNA is the downstream target of miR-877-5p.…”
Section: Discussionmentioning
confidence: 97%
“…It is found that miR-877-5p inhibits the cell proliferation, migration and invasion of hepatoma [40] and suppresses the cell growth of gastric carcinoma [39]. Also, more researches demonstrate that various long non-coding RNAs or circular RNAs facilitate the tumorgenesis of different carcinomas by decreasing the level of miR-877-5p [66][67][68][69][70], further verifying the suppressive effect of miR-877-5p in cancer development. In accordance with previous researches, the results of our experiments showed that TQ significantly upregulated the miR-877-5p expression level, and the inhibitor of miR-877-5p markedly upregulated the mRNA levels of CD274 (PD-L1), suggesting that CD274 mRNA is the downstream target of miR-877-5p.…”
Section: Discussionmentioning
confidence: 97%
“…We also identified miR-877-5p binding sites on circCCNT2. Interestingly, miR-877-5p and miR-877-3p have been reported to interact with several other circRNAs in relation to cancer progression [ 62 64 ]. However, this relationship has not previously been reported in the context of any neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“… 240 Expressions of exosomal circRNAs, such as circAKT3, has-circ-0004001, has-circ-0004123, has-circ-0075792, circ-0061395, and circTMEM45A are also highly upregulated in HCC patients. 241 243 However, exosomal circ-0051443 is downregulated in plasma exosomes from HCC patients, which exerts a role in inducing cell apoptosis and inhibiting malignant behaviors. 244 Wang et al reported that level of exosomal has-circ-0074854 is also downregulated in HCC patients and plays a role in inhibiting tumor cell migration and invasion by repressing M2 macrophage polarization.…”
Section: The Roles Of Exosomal Ncrnas In Human Diseasesmentioning
confidence: 99%